Impact of maternal and pre-existing antibodies on immunogenicity of inactivated rotavirus vaccines. Issue 28 (21st June 2022) - Zhou, Yan; Hu, Xiaoqing; Chen, Rong; Wu, Jinyuan; Lin, Xiaochen; Lu, Chenxing; Yin, Na; Tang, Yaya; Shi, Peng; Song, Zexin; Zhao, Yongmei; Sun, Maosheng; et al.
Abstract: Rotavirus (RV) is a major pathogen causing severe diarrhea in infants and children aged less than 5 years. Vaccination is an economically feasible and effective strategy to prevent rotavirus infections. However, immune efficacy of live vaccines could be interfered by maternal antibodies and pre-existing antibodies of children. To develop an inactivated rotavirus vaccine (IRV), we had previously isolated a wild-type human rotavirus strain ZTR-68-A (G1P[8]) from the fecal samples of infants having severe diarrhea in a region endemic for the presence of this pathogen. In our present study, we assessed whether the presence of maternal and pre-existing antibodies in newborn BALB/c mice affected the immunogenicity of IRV administered to these animals. Our results indicate that maternal antibodies, generated from either vaccine immunization or rotavirus infection, showed partial influence with the immune responses generated by two doses of IRV vaccination. Increasing the number of immunizations can significantly improve the titer of serum neutralizing antibody and a seroconversion rate of up to 100%. In newborn mice, single-virus infection did not elicit detectable levels of serum neutralizing antibodies. After an IRV vaccination, the immune responses of these mice remained unaffected, with no significant differences in titers compared with those of control-group mice. In summary, choosing a suitable immunization dose and dosing frequency is essential for the immune effectiveness of IRV. The results of this study will provide animal experimental support for the IRV clinical research in future.